A Look Back: Taking stock of public school choice in Kappan. (September 2021) - Preston, Teresa
In this monthly column, Kappan managing editor Teresa Preston explores how the magazine has covered the questions and controversies about school choice. Although many authors across the decades objected to the use of vouchers to pay private school tuition, those same authors lent support to the idea of choice among public schools. Advocates of public school choice have endorsed various models for providing choices, from alternative schools, to magnet schools, to charter schools .